Study of In-Memory computing and exploration of the concept in a 22nm 3D1T DRAM circuit - Lipphardt, Friedemann (My University, 2021)
Considering the possibility of calculating multiplication and addition of values stored in memory not only in CPU, but directly in-memory this survey and exploration of the concept evaluates the usefullness and performance of this technology, presenting one of many possible designs to achieve this goal using DRAM technology and compare it to similiar designs done in the SRAM space.